(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: There is no standard of therapy for diabetic optic neuropathy (DON) which takes into consideration the type and stage of the disease. Purpose: To assess the clinical efficacy of combined adjunct treatment with thioctic acid, a combination of vitamins В1, В6, and В12, ethyl methyl hydroxypyridine succinate, citicoline and brimonidine tartrate in the management of advanced-stage axial DON. Materials and Methods: Forty patients (63 eyes) were followed up after being diagnosed with advanced-stage axial DON. The adjunct group was composed of 20 patients (31 eyes) who were administered two courses a year of the following treatment as a combined adjunct to hypoglycemic therapy: 1) a 600 mg intramuscular injection of thioctic acid (Berlithion), daily for 21 days, followed by switching to oral regimen, at a dose of one 300 mg tablet twice a day for 21 days, (2) a 2 ml intramuscular injection of Milgamma, once per 3 days for 21 days, followed by switching to oral regimen, one tablet thrice a day for 21 days, (3) a 100 mg intramuscular injection of ethyl methyl hydroxypyridine succinate (Armadine), twice a day for 14 days, and (4) a 500-mg intravenous bolus of citicoline (Ceraxon), twice a day for 14 days, followed by switching to oral regimen, 500 mg daily for a month. In addition, they were administered topical brimonidine tartrate 0.2%, 1-2 drops twice a day on a constant basis. The control group (20 patients; 32 eyes) received hypoglycemic therapy only. In addition to routine eye examination, retinal and optic nerve optical coherence tomography and electrophysiology were performed. Patients underwent an examination at baseline and 1.5, 6, 7.5, 12, 13.5, 24 and 25.5 months after treatment. Results: The combined adjunct treatment was found to result in improvements in study indices in 83.9% of patients of the adjunct group, with 191% better visual acuity (p < 0.05), 235.0% lower electrically evoked phosphene thresholds (p < 0.05), 38.5% less ganglion cell complex (GCC) focal loss volume (FLV), and 36.5% less thickness of the lamina cribrosa compared to controls at 25.5 months. Conclusion: Our combination treatment was found to be clinically efficacious in improving structural and functional characteristics of the optic nerve in patients with advanced-stage axial DON.